Significance Assessment of Amphora coffeaeformis in Arsenic-Induced Hemato- Biochemical Alterations of African Catfish (Clarias gariepinus) - Mekkawy, Imam A.; Mahmoud, Usama M.; Moneeb, Rehab H.; Sayed, Alaa El-Din H. (Frontiers in Marine Science, 2020)
The heavy metals have different adverse impacts on different life stages of fish species with attempts to use natural antioxidants to counteract their effects. So, the present study investigated the potential protective effects of Amphora coffeaeformis extract against arsenic-induced hemato-biochemical alterations in African catfish, Clarias gariepinus. The fish exposed to sub-lethal concentrations of arsenic; 19.2 and 38.3 mg/l (1/8 and 1/4 of 96h-LC50 value, 153.17 mg/l) for 15 days. The significant main effect of arsenic was recorded in some blood parameters such as RBC’s count, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, and white blood cells. As regards the biochemical parameters, the arsenic main effect was significant for alkaline phosphatase, glucose, uric acid, creatinine, albumin, globulin, and albumin/globulin. Also, the residue of arsenic in fish muscles showed significant effects. These arsenic-induced parameters were improved with the dietary supplemented amphora. So, Amphora extract can be used as detoxification factor on fishes induced by arsenic due to its biologically active components working as antioxidant, antiviral, antibacterial and anti-inflammatory besides the excellent contents of proteins and carbohydrates which enhance these components.